Pandangan Alam dalam Cerpen Kamisama karya Kawakami Hiromi - Ambarastuti, Retno Dewi; Savitri, Laily Amalia; Chotimah, Amalia; Choiro, I’ir Hikmatul (Puitika, 2023)
This literary research uses a short story entitle Kamisama by Kawakami Hiroshi. Kamisama tells the Watashi’s short journey with Kuma on a spring day. Kuma is a bear who recently moves in a lives next door to Watashi’s apato room. Despite being a bear, Kuma can speak human language and behave like humans. Kamisama not only tells the condition of the natural environment, but also contains a picture of the life of Japanese people related to Japanese culture, in the form of daily habits, view of life, and Japanese people’s thoughts about nature and environment. The research conveys how the natural and cultural views of Japanese society in the Kamisama short story. This study uses qualitative descriptive methods, ecocriticism in Japanese literature and culture. The results this study shows the literary ecocriticism aspect in the interaction between characters in the environment. Ecosystem of the natural environment are not used by humans, but their existence is also respected.